2020
DOI: 10.3389/fmicb.2020.00854
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity and Mode of Action of Miltefosine Against Clinical Isolates of Candida krusei

Abstract: Candida krusei attracts attention from medical professionals mainly for its intrinsic resistance to fluconazole and the limited number of drugs available to treat C. krusei vulvovaginal candidiasis. Miltefosine was demonstrated to have good antifungal activity both in vitro and in vivo. Here, we determined the susceptibility profiles of 57 clinical C. krusei isolates from vulvovaginal candidiasis patients and assessed the antifungal activity of miltefosine against C. krusei. All isolates were susceptible to vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 40 publications
4
17
1
3
Order By: Relevance
“…In contrast to our results, miltefosine has been reported to have synergy with posaconazole against Fusarium oxysporum and the mucormycetes (118). In addition, a recent study with C. auris demonstrated that for 25% of the isolates assessed there was a synergic activity between miltefosine and amphothericin B, with FICI=0.5 (110).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our results, miltefosine has been reported to have synergy with posaconazole against Fusarium oxysporum and the mucormycetes (118). In addition, a recent study with C. auris demonstrated that for 25% of the isolates assessed there was a synergic activity between miltefosine and amphothericin B, with FICI=0.5 (110).…”
Section: Discussioncontrasting
confidence: 99%
“…The interaction assay between miltefosine and myriocin showed that at high concentrations of both compounds, the FICI value was greater than 4.0 characterizing an antagonistic effect between these drugs (76). This implicates that sphingolipid metabolism may be important to the antifungal effect of miltefosine, corroborating with previous results obtained for other fungal species and trypanosomatids (77,78,105,110).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Exogenous ergosterol addition competes with the target on the C. neoformans and Candida krusei membrane and increases the miltefosine MIC (Spadari et al, 2018;Wu et al, 2020). Because GlcCer, a sphingolipid well studied in Scedosporium and Lomentospora species, plays crucial roles in fungal growth and virulence and is a component of lipid rafts, we decided to check whether it could cause the same effect.…”
Section: Discussionmentioning
confidence: 99%